The Role of University Professors’ Emotional Competencies in Students’ Academic and Psychological Well-Being: A Systematic Review - Camilla Brandao De Souza; Alessandra Cecilia Jacomuzzi (Education Sciences)
In higher education, the emotional intelligence (EI) of university professors, defined as the ability to perceive, understand, manage and utilize emotions effectively, is increasingly recognized as a pivotal factor in enhancing students’ academic achievement and psychological well-being. However, the scarcity of studies directly linking professors’ EI to students’ well-being highlights a critical research gap. This systematic review investigates how professors’ emotional competencies influence student outcomes—such as academic performance, engagement, motivation, and mental health—and identifies the factors that mediate or moderate these effects. Findings indicate that professors’ EI, particularly empathy, emotional regulation, and interpersonal skills, significantly enhances student engagement, motivation, and academic satisfaction, with indirect effects on psychological well-being. Cultural context, teaching modality (e.g., online vs. in-person), and professors’ age and experience moderate these effects and influence effect sizes. Qualitative synthesis further highlighted contextual gaps in the literature. The limited focus on well-being and outcomes and reliance on self-report measures underscore the need for longitudinal, culturally diverse studies and performance-based EI assessments. The value of this research lies in its potential to inform evidence-based educational practices and institutional policies. By elucidating the role of professors’ EI, the review lays the groundwork for developing faculty training programs aimed at strengthening emotional competencies and fostering inclusive, supportive learning environments that promote student growth and resilience. This is especially relevant given the growing prevalence of stress, anxiety, and disengagement among university students, exacerbated by post-pandemic challenges and academic pressures. Understanding the impact of EI can inform culturally responsive interventions, improve student retention, and enhance institutional effectiveness, thereby addressing a pressing need in contemporary higher education. In today’s rapidly evolving technological, social, and cultural landscape, universities have both the opportunity and the responsibility to act as catalysts for the creation of an educational culture that promotes social well-being. This requires adopting educational and organizational models that prioritize human care and the quality of interpersonal relationships. To be effective, these priorities must be integrated into all university operations, from governance to student support and talent development.